A WITNESS UNTO ITSELF THE INTEGRITY OF THE AUTOGRAPH MANUSCRIPT OF FELIPE GUAMAN POMA DE AYALA’S EL PRIMER NUEVA CORÓNICA Y BUEN GOBIERNO (1615/1616) - Adorno, Rolena (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2002)
-